Language style in serat piwulang Hamengkubuwana 1 manuscript - Listiyapinto, Ravi Zamzam; Endraswara, Suwardi (Yayasan Mitra Persada Nusantara, 2024)
This research attempts to describe how language style is used in Serat Piwulang Hamengkubuwana 1. Modern philological research techniques and qualitative descriptive methodologies are both used in this work. The Serat Piwulang Hamengkubuwana 1 collection manuscript and text with the reference code MS 12337 from the British Library served as the basis for the research. The method of data collecting was philology. Semantic validity is employed, while interrater reliability is used for reliability. This research produces 3 things. The manuscript description describes the state of the manuscriptLessons from Hamengkubuwana 1 still good, part of the text is also clear to read. Only a few defective parts of the text were found. Translate text with text transliteration, namely changing Javanese script writing into Latin writing. Text translation is done by changing the Kawi and Javanese languages into Indonesian so that they are more general in nature. Explain the style of language used in the textLessons from Hamengkubuwana 1. The style of language used is taken from the repertoire of Indonesian and Javanese.